Les récits de la mort d’Henri III publiés en Angleterre : régicide et fabrication de l’histoire dans les années 1590 - Marie-Céline Daniel (Etudes Epistémè)
The news of Henri III’s death contained all the ingredients of a perfect story, yet it did not lead to the publication of many pamphlets in London. The English authorities seem to have believed that the printed output had to be watched carefully, and the information selected so as to leave the king’s death out of focus. Like a prism, these texts directed the readers’ gaze away from the main event. The regicide was re-examined by English historiographers only at the end of the century, after the kingdom of France was “pacified” by Henri IV. Yet, these history texts usually took over factual elements that had been introduced in the earlier accounts of the king’s murder, even when these facts were inaccurate. It is therefore accurate to talk about history making, through a poetics of catastrophe which was heavily influenced by the English authorities.